Inter‐decadal variations in El Niño–Southern Oscillation impacts on the autumn precipitation in the eastern China. (13th June 2019) - Yuan, Chaoxia; Wang, Deng
Abstract: By using the observation, reanalysis data and numerical simulation, the inter‐decadal variations in El Niño–Southern Oscillation (ENSO) impacts on the eastern China (EC) precipitation during its developing autumn in the past 65 years have been investigated. Results show that ENSO is related to the significant dipole precipitation anomalies in EC in the early decades (1951–1981); El Niño/La Niña introduces more/less precipitation in the southern EC, but less/more in the northern EC. However, the significant dipole pattern disappears in the recent decades (1985–2015), mainly owing to loss of the significant positive influences of La Niña on the northern EC precipitation. Comparison of the atmospheric circulation anomalies in East Asia related to La Niña in the two periods shows that there are anticyclonic circulation anomalies in the northeastern Asia near Japan in the first period, while they shift to Mongolia in the second period. Hence, in the first period, the northern EC is under the influences of anomalous southwesterlies along the southwestern flank of the anticyclonic circulation anomalies that advect more moisture from the south to the northern EC and lead to more precipitation there. In contrast, in the second period, the northern EC is under the influences of anomalous northeasterlies along the southeastern edge of the anticyclonic circulation anomalies near Mongolia that impede the northwards transport of moisture and are not conducive to surplus precipitation. The westwards shift of the anticyclonic circulation anomalies may be closely related to the higher SST and thus convective anomalies related to La Niña in the tropical western North Pacific (WNP) east of the Philippines in the second than the first periods. The sensitivity experiment forced by the positive SST anomalies in the tropical WNP comparable to the observed in an atmospheric general circulation model can successfully simulate the anticyclonic circulation anomalies around Mongolia. Abstract : We have discovered that ENSO caused the significant dipole autumn precipitation anomalies in eastern China (EC) in the early decades (1951–1981); El Niño/La Niña introduces more/less precipitation in the southern EC, but less/more in the northern EC. However, the significant dipole pattern disappears in the recent decades (1985–2015). The decadal variations in the ENSO impacts are due to the decadal changes of SST anomalies related to La Niña in the tropical western North Pacific. In the figure, composite anomalies of SON precipitation (mm/day) in (a, c) El Niño and (b, d) La Niña years during (a, b) the first and (c, d) second periods, respectively. The anomalies significant at the 90% confidence level are stippled.